Wildlife Trafficking the illicit trade in wildlife, animal parts, and derivatives - Ege, Gian; Schloenhardt, Andreas; Schwarzenegger, Christian (sui generis, 2020)
"Wildlife trafficking threatens the existence of many plant and animal species and accelerates the destruction of wildlife, forests, and other natural resources. It contributes to environmental degradation, destroys unique natural habitats, and deprives many countries and their populations of scarce renewable resources. Nevertheless, preventing and supressing the illegal trade in wildlife, animal parts, and plants is presently not a priority in many countries and it remains overlooked and poorly researched. The chapters included in this volume address causes, characteristics, and actors of wildlife trafficking, analyse detection methods, and explore different international and national legal frameworks."